2022
DOI: 10.3390/ijms231911894
|View full text |Cite
|
Sign up to set email alerts
|

NOD2 Signaling Circuitry during Allergen Sensitization Does Not Worsen Experimental Neutrophilic Asthma but Promotes a Th2/Th17 Profile in Asthma Patients but Not Healthy Subjects

Abstract: Nucleotide-binding oligomerization domain 2 (NOD2) recognizes pathogens associated with the development of asthma. Moreover, NOD2 adjuvants are used in vaccine design to boost immune responses. Muramyl di-peptide (MDP) is a NOD2 ligand, which is able to promote Th2/Th17 responses. Furthermore, polymorphisms of the NOD2 receptor are associated with allergy and asthma development. This study aimed to evaluate if MDP given as an adjuvant during allergen sensitization may worsen the development of Th2/Th17 respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…PheWAS results also revealed interesting pleiotropic effects of these genes, which have been shown to exert relevant functions in the identified phenotypes, such as the associations of NOD2 and hypercoagulability (286.81 and 286.8) [61] and asthma (495) [62], IL6ST and joint disease (727.4) [63] and systemic and cutaneous lupus erythematosus (695.4, 695.42, and 695.41) [64], and IFNAR1 and viral hepatitis [65]. Moreover, candidate genes displayed associations with various other autoimmune and allergic conditions, including ankylosing spondylitis, enthesopathy, rheumatoid arthritis, erythematous skin lesions, eosinophilia, and polyarteritis nodosa.…”
Section: Phewasmentioning
confidence: 93%
“…PheWAS results also revealed interesting pleiotropic effects of these genes, which have been shown to exert relevant functions in the identified phenotypes, such as the associations of NOD2 and hypercoagulability (286.81 and 286.8) [61] and asthma (495) [62], IL6ST and joint disease (727.4) [63] and systemic and cutaneous lupus erythematosus (695.4, 695.42, and 695.41) [64], and IFNAR1 and viral hepatitis [65]. Moreover, candidate genes displayed associations with various other autoimmune and allergic conditions, including ankylosing spondylitis, enthesopathy, rheumatoid arthritis, erythematous skin lesions, eosinophilia, and polyarteritis nodosa.…”
Section: Phewasmentioning
confidence: 93%
“…Taking the origin of natural SCFAs in human organisms into account, this could stimulate the development of personalized nutritional therapeutic approaches against allergies, autoimmune, and other chronic inflammatory disorders. Bouté and colleagues [4] observed that the co-stimulation of nucleotide-binding oligomerization domain 2 (NOD2) with muramyl di-peptide (MDP) during allergen sensitization did not worsen Th2/Th17-type allergic airway inflammation in a mouse model; however, MDP co-stimulation of allergen-primed dendritic cells (DCs) promoted a Th2/Th17 profile in asthma patients but not in healthy subjects. Considering that NOD2 adjuvants are used in vaccine design to boost immune responses, whereas care needs to be taken in asthmatics, those might be used in non-sensitized individuals.…”
mentioning
confidence: 99%